Findings from an OMFS journal club: is COVID-19 the catalyst we have needed to embrace technology?. Issue 1 (January 2022) - Aulakh, G.S.; Duggal, S.; Sutton, D.
Abstract: The COVID-19 outbreak has rapidly progressed into a worldwide pandemic, and the need for social distancing has changed the way we learn and work. Our monthly OMFS journal club has been no different, and is currently meeting on the video conferencing application Microsoft Teams. The use of a virtual setting for training in medicine and dentistry is not new and, as in the case of our recent move to a virtual medium, it may be that COVID-19 has fast-tracked this digital transformation. There are of course disadvantages to online teaching that traditional face-to-face teaching overcomes. We conducted a survey to examine how trainees' attitudes and experiences have altered with this change, and to understand whether some elements of this new style of training may be advantageous in the post-pandemic world. We aimed to assess trainees' attitudes towards online teaching, and which elements, if any, would be beneficial once face-to-face teaching becomes possible again. A survey was created for all trainees taking part in journal club meetings at Bradford Teaching Hospitals. Multiple-choice and Likert scale questions were designed to ascertain the differences in experience between online and face-to-face settings. A Wilcoxon matched pairs signed test was used to analyse the results. Responses were kept anonymous. Results showed that the majority of trainees found it easier to attend the online journal club, and also indicated that the most found Microsoft Teams easy to use, though we did not have another online application for comparison. There was no significant difference in participation comfort between the two settings, though trainees felt that the online setting considerably improved learning effectiveness. Furthermore, 79% (11/14) thought that online tutorials and meetings should replace traditional face-to-face meetings in the future. The use of internet technology such as video conferencing is not new, and although journal clubs are typically held in academic institutions, online and virtual clubs are flourishing. With an array of advantages, there is no shying away from the trend to move our teaching to a virtual medium. COVID-19 may have just provided the stimulus that has forced this transformation to accelerate.